Generation of Aromas and Flavours - Vilela, Alice (IntechOpen, 2018)
Consumer product acceptance and market success are dependent on the product's aroma/flavour. Flavours can be produced through chemical synthesis, microbial biocatalysis or by extraction from plants and animal sources. In recent times, chemical synthesis is not as desirable as this is not eco-friendly. So, in the food industry, natural ingredients are added to preparations for efficiency, softness or emotional appeal. Microbiology, bioengineering and biochemistry have enabled the elucidation of metabolic pathways; genetic engineering is expected to help in identifying metabolic blockages and creating novel high-yielding strains, while proteomics help in the application of analytical techniques. All these sciences, old and new, will lead to innovative ideas in the quest for better, sustainable and consumer-approved flavours and aromas.